Pengalaman Perawat Komunitas Dalam Melakukan Penanganan Kegawatdaruratan Psikiatri Pada Anak Dengan Child Maltreatment - Hidayah, Nurul; Seprian, Dwin; Florensa, Ns. (Universitas Malahayati Bandar Lampung, 2022)
Background: Proper and fast handling of emergency conditions is the key to patient safety. Emergency conditions are conditions where there is a sudden disruption of physiological or psychological integrity and can threaten safety. As a primary health care provider, you are not only required to be alert and ready to face physical emergencies, but also psychiatric emergencies. Psychiatric emergency conditions are as important as other physical emergency conditions, prompt and appropriate treatment can save patients from conditions that threaten their life safety. Some psychiatric emergency conditions include conditions of attempted suicide, restlessness, panic attacks, aggressive behavior changes to disturb the surrounding conditions and the environment. Psychiatric emergency conditions can occur in all service units, understanding of the handling of psychiatric emergencies must be understood holistically by all officers, especially nurses in primary health care facilities. Objective: to explore the life experiences of community nurses in handling psychiatric emergencies in children with child maltreatment in primary health care facilities in Pontianak city. Methods: This research design uses a qualitative descriptive approach with a descriptive phenomenological approach. The population in this study is Community Nurses in Primary Health Facility Services in Pontianak City. The number of participants was determined through purposive sampling technique. The nurse's experience was explored through in-depth interviews and data analysis using the Colaizzi method. The target output of this research is expected to be published in national journals. Results: This study provides an overview of the experience of community nurses in handling psychiatric emergencies in children with child maltreatment in primary health care facilities in the city of Pontianak. The nurse's experience is described in 2 themes: 1) Handling that is not comprehensive and cross-sectoral collaboration and 2) The lack of competence of human resources and facilities and infrastructure. Conclusion: There is still a lack of trained personnel, infrastructure facilities are also still lacking, from the process of handling psychiatric emergencies Child Maltreatment in Primary Health Facility Services still does not follow the management concept of implementing a puskesmas that provides comprehensive services. Suggestion: It is hoped that policy makers will be able to issue SK or regional regulations related to the implementation of handling child maltreatment psychiatric emergencies in primary health care facilities and further improve efforts to develop and supervise implementation in handling psychiatric emergencies child maltreatment in primary health care facilities. Keywords:Children,Emergency,Psychiatry ABSTRAK Penanganan kondisi gawat darurat yang tepat dan cepat menjadi kunci keselamatan pasien. Kondisi gawat darurat adalah kondisi dimana terjadi gangguan integritas fisiologis atau psikologis secara mendadak dan dapat mengancam keselamatan. Sebagai penyedia layanan kesehatan primer tidak hanya dituntut untuk sigap dan siap menghadapi kondisi kegawat daruratan fisik, namun juga kondisi kegawatdaruratan psikiatri. Kondisi kegawat daruratan psikiatri sama pentingnya dengan kondisi gawat darurat fisik lainnya, penanganan yang cepat dan tepat dapat menyelamatkan pasien dari kondisi yang mengancam keselamatan jiwanya.Beberapa kondisi gawat darurat psikiatrik meliputi kondisi percobaan bunuh diri, gaduh gelisah, serangan panik, perubahan tingkah laku yang agresif hingga mengganggu kondisi sekitar dan lingkungan. Kondisi gawat darurat psikiatri dapat terjadi di seluruh unit pelayanan, pemahaman mengenai penanganan gawat darurat psikiatri harus dipahami secara holistik oleh seluruh petugas khusunya perawat di fasilitas pelayanan Kesehatan primer. Tujuan penelitian ini yaitu untuk mengeksplorasi pengalaman hidup Perawat Komunitas Dalam Melakukan Penanganan Kegawatdaruratan Psikiatri Pada Anak dengan child maltreatment Di Pelayanan Fasilitas Kesehatan Primer Di Kota Pontianak. Rancangan penelitian ini menggunakan deskriptif kualitatif dengan pendekatan fenomenologi deskriptif. Populasi dalam penelitian yaitu Perawat Komunitas Di Pelayanan Fasilitas Kesehatan Primer Di Kota Pontianak. Jumlah partisipan ditentukan melalui teknik purposive sampling. Pengalaman perawat digali melalui wawancara mendalam dan analisa data menggunakan metode Colaizzi.Target luaran penelitian ini diharapkan dapat dipublikasin pada jurnal nasional. Hasil penelitian ini memberikan gambaran mengenai Pengalaman Perawat Komunitas Dalam Melakukan Penanganan Kegawatdaruratan Psikiatri Pada Anak Dengan Child Maltreatment Di Pelayanan Fasilitas Kesehatan Primer Di Kota Pontianak. Pengalaman perawat tersebut digambarkan dalam 2 tema : 1)Penanganan yang belum komperhensif dan kerjasama lintas sektor serta 2) Minimnya kompetensi SDM serta sarana dan prasarana. Kata Kunci :Anak ,Gawat Darurat,Psikiatri